Mortalidade em efetivos da polícia militar do Estado de São Paulo - Merino, Paulo Sérgio [UNIFESP] (2010)
Justification: The few national studies about police mortality show higher rates of death from external causes compared to the general population. Most of international research reports similar results. In their conclusions, these studies show the police profession as a risk factor for violent deaths, diseases of the circulatory system, neoplasms and disorders arising from emotional distress. Objectives: To calculate the mortality rate of the International Diseases Classification chapters (IDC-10th revision) of police officers from the Military Police of Sao Paulo, active duty, between 2002 and 2006, and compare them to the population of Sao Paulo state. Method; The policemen and population deaths were provided by the State System of Data Analysis of the State of Sao Paulo (SEADE) and the Brazilian Health Ministry, respectively. Results: The overall mortality rate of policemen was lower than the population (247.1 from 450.5 deaths per 100 thousand people), possibly, this reduction was result of the hiring process that selects healthier police than population average. However, the rate of natural deaths causes defined among policemen aged more than 44 years, as infectious and parasitic diseases; endocrine, nutritional and metabolic diseases, circulatory and digestive diseases; cancer and mental and behavioral disorders, was higher than the population. With regard to external causes category, the rate of police officers was 11% higher, especially the suicide rate was twice and traffic accidents, 26% higher. The soldiers reached higher mortality rates than their superiors. Conclusion: The military police activity exposes its members to the risk of death by violence deaths, and tends to increase the natural death rate after 44 years old.